Travelling with heart failure: risk assessment and practical recommendations - Haehling, Stephan von; Birner, Christoph; Dworatzek, Elke; Frantz, Stefan; Hellenkamp, Kristian; Israel, Carsten W.; Kempf, Tibor; Klein, Hermann H.; Knosalla, Christoph; Laufs, Ulrich; Raake, Philip; Wachter, Rolf; et al. (Nature reviews. Cardiology, 2022)
Patients with heart failure are at a higher risk of cardiovascular events compared with the general population, particularly during domestic or international travel. Patients with heart failure should adhere to specific recommendations during travel to lower their risk of developing heart failure symptoms. In this Review, we aim to provide clinicians with a set of guidelines for patients with heart failure embarking on national or international travel. Considerations when choosing a travel destination include travel distance and time, the season upon arrival, air pollution levels, jet lag and altitude level because all these factors can increase the risk of symptom development in patients with heart failure. In particular, volume depletion is of major concern while travelling given that it can contribute to worsening heart failure symptoms. Pre-travel risk assessment should be performed by a clinician 4-6 weeks before departure, and patients should receive advice on potential travel-related illness and on strategies to prevent volume depletion. Oxygen supplementation might be useful for patients who are very symptomatic. Upon arrival at the destination, potential drug-induced photosensitivity (particularly in tropical destinations) and risks associated with the local cuisine require consideration. Special recommendations are needed for patients with cardiac implantable electronic devices or left ventricular assist devices as well as for those who have undergone major cardiac surgery.